Impact of High Frequency Trading on Equity Market with Reference to NSE India - Kotishwar, A. (Indian Journal of Finance, 2020)
.The study focused on the high-frequency trading impact on the stock market. The study considered the 1 minute, 5 minutes, 10 minutes, 15 minutes, 30 minutes, and 1 hour time periods. The study considered the historical time-series data from NSE India for the period of three months, that is, April-June 2019. The ARCH method was applied with the GARCH, and the results indicated that the Nifty volatility had a significant impact on the Bank Nifty volatility. The ordinary least square method results indicated that the Nifty 1 minute had a greater effect than the other time periods on the Bank Nifty.